Adsorption of collectors on model surface of Wiser bituminous coal: A molecular dynamics simulation study. (August 2015) - Zhang, Zhiqiang; Wang, Caili; Yan, Kefeng
Highlights: The adsorption mechanism of three oily collectors on coal surface was modeled. All these collectors could repel the interfacial water molecules. Dodecane is much more effective in improving the surface hydrophobicity of coal. Abstract: Coal flotation makes use of the hydrophobicity of coal surface. To enhance the hydrophobicity of coal particles, oily collectors are usually added. Although collectors have been widely applied in coal processing, the microscopic collection mechanism remains a formidable task due to the complexity of coal surface structure. In this work, different combined systems formed by collectors, water and a model surface of Wiser bituminous coal have been studied using molecular dynamics calculations. We modeled the interaction of each collector oil droplet with the coal surface in aqueous phase. In addition, water/collector model systems were also considered in order to reproduce the interaction of the different collectors with water molecules in the collector adsorption process. The results indicate that all three collectors, i.e. dodecane, nonylbenzene and nonylphenol, form spherical insoluble oil droplet in aqueous phase. After the addition of collector droplet over coal surface, all these collectors could thermodynamically repel the interfacial water molecules and spread over the coal surface, thereby reducing roughness of coal surface. The adsorption of nonylphenol on coal surface via both π–π stacking and hydrogen bonds is most favorable, followed by that of nonylbenzene and dodecane. The presence of collector on the coal surface could improve the hydrophobicity. The number of hydrogen bond between water and modified coal surface decreases and the mobility of water molecules increases compared to the original coal surface. However, the extent of hydrophobicity of modified coal surface by these collectors is inconsistent with their adsorption capabilities. Nonylphenol is the worst collector to improve the surface hydrophobicity of coal as part of nonylphenol molecules orient away from coal surface to form hydrogen bonds via their hydroxyl groups with water molecules. Dodecane should be the most effective collector as the hydration energy of the modified surface and the number of formed hydrogen bond between this surface and water molecules are the lowest, whereas the mobility of water molecules on this modified surface is the highest.